Towards an identification of “Linguistic Unease” (Atti del Sodalizio Glottologico Milanese, 2019)
This paper argues that the assessment of sociolinguistic justice should pass through the promotion of linguistic ease, analysed through a number of sociolinguistic parameters already in use for the repertoires of multilingual communities. Their consideration makes it possible to focus on complexity of globalising and localising forces, beyond the West phalian model of nation-state. In particular, three axes of analysis should be taken into account: the formality of situations; the sense of belonging; special domains, like school and writing. KEYWORDS: Sociolinguistics, linguistic repertoire, linguistic justice, linguistic unease